Maternal mortality : report of meeting held at Friends' House. Euston Road on November 15, 1932 (London : Maternal Mortality Committee)
1932-11 1932 1930s 36 pages But I want to stress another point. We are quite right to surround the expectant mother with every kind of care, but we are tending to leave out the human element. Childbirth is not just a major operation, it is a wonderful time of emotional stress of the first magnitude, a time of joy in anticipation, joy in realisation. Joy should be, and is, the vital factor. Modern routine practice in well-to-do homes tends to deprive a mother of this. The baby is carried off into another room. The reign perhaps of Truby King begins! We need to go back to Nature, and to maintain after birth that close connection between mother and child which is their best safeguard against infection. The proper place for the baby is in its mother's arms — the midwife often has no option, but the maternity nurse with rooms and comforts at her command may and generally does arrange otherwise to the infinite loss of both mother and child. DR. EDITH SUMMERSKILL (Wood Green Labour Party) : It is rather surprising this afternoon that we have not among us one of those much maligned people called general medical practitioners. I worked in a congested area in London for about six years, attending women in their confinements under conditions which seem almost dreadful when I think of them now, and I am not old. I am talking about a few years ago. I want you to bear in mind that a general practitioner does about 50 per cent. of all the midwifery, and he has not been represented here. If a general practitioner is called to a confinement case in the middle of surgery hours, he leaves the case he is dealing with whatever it may be — or he does not leave it — and he goes and attends to the woman. He can't stay there for the whole of the labour so he goes back to his surgery and perhaps opens an abscess there. That is what happens every day in London in doctors' surgeries. He finishes his busy surgery hours and rushes back to the confinement to a room perhaps where it is almost impossible to obtain hot water. I have waited half an hour sometimes for hot water. These are the conditions under which midwifery is conducted. These are the facts I am telling you. In my opinion midwifery should be regarded in the same light as a surgical operation. Nobody suggests performing an operation upon a woman in a room where there are five to eleven people living. I have confined a woman with three or four children present in the room. There are 33,000 families living five in one room in London. At midnight were [where] can you put the rest of the family? Nowhere. Those are the conditions. This is my suggestion. This is the only remedy. There should be hospital accommodation for every maternity case. Every maternity case should be regarded with just as much seriousness as a surgical operation, and the (27) 292/824/1/45